Comparison of Tannin Concentration on Fresh and Dried Tea Leaf (Camelia sinensis L.) Extract Using UV-Visible Spectrophotometric Method - Youstiana Dwi Rusita; Pradea Indah Lukito; Ratih Purwasih; Rina Indriani (LPPM Universitas Duta Bangsa Surakarta, 2019)
One of herbal plants that is cultivated as a material for making traditional medicines is tea (Camelia sinensis L.). Parts of plants that are used as traditional medicine were fresh or dried leaves. Tea leaves contain tannins which are known as active compound used to treat diarrhea, stop bledding and treat hemorrhoids. This research aimed to determine tannin concentration on fresh and dried tea leaf extract using UV-Visible spectrophotometric method. The type of this research used quantitative research with experimental design use t-test. This research used a sampling technique that is purposive sampling. The results of the analysis of tannin concentration using UV-Visible spectrophotometric method on fresh and dried tea leaf extract were 3,64 ± 0,105276 mg GAE/gram sample and 3,87 ± 0,019088 mg GAE/gram sample respectively. Tannin concentration on dried tea leaf extract was higher than on fresh tea leaf extract. After was analyzed statistically with independent sample test (T-test), the result showed that tannin concentration on fresh and dried tea leaf extract were unsignifficantly different. Because of the value of sig was 0.052 > 0.05.